Reduced glucocorticoid production rate, decreased 5alpha-reductase activity, and adipose tissue insulin sensitization after weight loss. - Tomlinson, J; Finney, J; Hughes, B; Hughes, S; Stewart, P (2008)
OBJECTIVE: The epidemics of obesity, insulin resistance, and type 2 diabetes have heightened the need to understand mechanisms that contribute to their pathogenesis. Increased endogenous glucocorticoid production has been implicated based on parallels with Cushing's syndrome. We have assessed the impact of weight loss on glucocorticoid secretion and metabolism (notably 11beta-hydroxysteroid dehydrogenase type 1 and 5alpha-reductase [5alphaR] activity) and insulin sensitivity. RESEARCH DESIGN AND METHODS: Twenty obese volunteers were investigated before and after weight loss. Patients underwent hyperinsulinemic-euglycemic clamps with simultaneous adipose microdialysis and oral cortisone acetate administration. Changes in glucocorticoid secretion and metabolism were assessed using 24-h urine collections. RESULTS: Before weight loss, fat mass correlated with glucocorticoid secretion rate (total fat, r = 0.46, P < 0.05; trunk fat, r = 0.52, P < 0.05); however, glucocorticoid secretion rate was inversely related to insulin sensitivity (r = -0.51, P < 0.05). Hyperinsulinemia failed to suppress adipose tissue interstitial fluid glycerol release (180 +/- 50 micromol [basal] vs. 153 +/- 10 micromol [steady state], NS). After oral cortisone (25 mg), cortisol concentrations within adipose interstitial fluid increased (4.3 +/- 1.1 vs. 14.2 +/- 2.6 nmol/l, P < 0.01), but glycerol concentrations did not change. After weight loss, insulin sensitivity increased. Consistent with insulin sensitization, adipose tissue interstitial fluid glycerol concentrations fell under hyperinsulinemic conditions (186 +/- 16 vs. 117 +/- 9 micromol, P < 0.05). Glucocorticoid secretion decreased (11,751 +/- 1,520 vs. 7,464 +/- 937 microg/24 h, P < 0.05) as did 5alphaR activity (5alpha-tetrahydrocortisol-to-tetrahydrocortisol ratio 1.41 +/- 0.16 vs. 1.12 +/- 0.17, P < 0.005). CONCLUSIONS: Obesity is associated with insulin resistance within adipose tissue and increased cortisol secretion rates; both are reversed with weight loss. Reduced 5alphaR activity after weight loss may decrease hypothalamo-pituitary-adrenal axis activation and reduce glucocorticoid metabolite production.